Pengaruh Edukasi Terhadap Pengetahuan, Minat dan Pengambilan Keputusan Penggunaan Metode Kontrasepsi Jangka Panjang Pada Ibu Hamil Resiko Tinggi - Kholifatur Rizkiyah, Nur; Puspitasari, Yenny; Ambarika, Rahmania (Jurnal Locus Penelitian dan Pengabdian, 2025)
Long-term Contraceptive Method is a contraceptive that can be used for more than two years, effective and efficient for the purpose of ending pregnancy or no longer wanting to have more children. The limited information received by prospective KB acceptors affects pregnant women in making decisions about choosing postpartum contraceptive methods. This study is an analytical study, namely to analyze the Effect of KB Education on Knowledge, Interest and Decision Making for the Use of MKJP KB in Pregnant Women Resti with a sample of pregnant women at the Obsgyn Polyclinic at Ngudi Waluyo Hospital in Wlingi, Blitar Regency. The research design with a classic experiment, is to group research subjects (commonly called respondents) into experimental groups and control groups. The results showed that KB education significantly increased the knowledge of pregnant women about the use of long-term contraceptive methods (MKJP), with an increase in knowledge scores from 55.75 to 61.88 (p = 0.000), while the group without education did not experience significant changes. In addition, interest in using MKJP KB also increased significantly after education, from an average of 25.05 to 29.18 (p = 0.000), while the group without education did not show significant changes. However, although knowledge and interest increased, decision-making to use MKJP actually decreased significantly from 16.40 to 14.78 (p = 0.005) in the group given education, while the group without education did not experience significant changes. This indicates that other factors such as social pressure and family support also influence pregnant women's decisions to use MKJP, so that education is effective in increasing knowledge and interest, but not always directly proportional to decision-making to use MKJP KB.